SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) DALAM PERJANJIAN KREDIT PERBANKAN DI KOTA DENPASAR - Wiryanta, I Putu Deny; Mertha, I Ketut; Puryatma, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 2 (2016), 2016)
The Law No. 4 of 1996 on Encumbrance Right (UUHT) aims to provide a foundation that enabling enactment of a powerful Encumbrance Right institutions, including the position of Procuration of Encumbrance Right Charging (SKMHT). In Article 15, Paragraph (3) and (4) UUHT declared a period of time for SKMHT for land rights were already registered and not registered yet. In fact, losses experienced by the debtor often occur as a result of that provision. The losses were partly a result of the expiration of SKMHT because of Encumbrance Right Deed (APHT) getting process had been exceeded the period of SKMHT validity, so that creditors do not have yet a certain guarantee binding deed of the guarantee provided by the debtor, which resulted in the arrest of the funds that will be allocated to debtor and the debtor it is becoming difficult to practice business activities. Based on this problem, the problem that can be formulated is how the legal result of the implementation of the Procuration of Encumbrance Right Charging (SKMHT) in banking loan agreement and What are the constraints in the implementation of the Procuration of Encumbrance Right Charging (SKMHT) in banking loan agreement as well as how to overcome the efforts in particular in Denpasar City. This type of research used in this thesis is empirical legal research with the consideration that the starting point of the research is the analysis of the gap between das sein sollen and the effectiveness SKMHT in which the banking loan agreement whereas SKMHT regulated under Article 15 UUHT. In Article 15, Paragraph (3) and (4) UUHT declared a period of time for SKMHT to land rights were already registered and not registered. In fact, losses experienced by the debtor often occur as a result of that provision . The losses were partly a result of the expiration of SKMHT because of Encumbrance Right Deed (APHT) getting process had been exceeded the period of SKMHT validity . The resultsof research areeffortsundertakento overcomethese obstacles, by renewingSKMHTwhichhas expired. Thus, overcomingbothof these obstaclesis only can be done byrenewingSKMHTwhile waiting the certificating process ofunregistered SKMHTobject. Once thecertificate of land rightis issued, thenbasedon SKMHT, the encumbrance right charging of SKMHT object is done so it became the object of encumbrance right.
Keywords: effectiveness, Encumbrance Right, Procuration, Period, Agreement